2019
DOI: 10.26614/les-wood.2019.v68n01a01
|View full text |Cite
|
Sign up to set email alerts
|

Tree-rings in Mediterranean pines – can we ascribe them to calendar years?

Abstract: IzvlečekAbstract: A tree ring is defined as a band of xylem-cell layers produced in one year. In Mediterranean trees cambium often produces several bands of alternating early-and latewood during one calendar year, resulting in Intra-Annual Density Fluctuations (IADFs). We present some characteristics of growth layers in Pinus pinea (stone pine) growing on Vesuvius Mountain (near Naples, Italy). would be classified as tree ring 2015. We also showed differences in cambium activity in late autumn between years: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…They are characterised by latewood-like cells in earlywood (E-IADF), and earlywood like cells in different portions of latewood (L-IADF) ( Figure 4). The species often have unclear growth ring bound- aries (Figure 4b) which are a consequence of uninterrupted cambial production in winter (De Luis et al, 2007De Micco et al, 2016a;Novak et al, 2016a;Balzano et al, 2018Balzano et al, , 2019a, and lack of cambial dormancy in winter (Prislan et al, 2016). The species can also contain dark rings (Figure 4b), i.e.…”
Section: Growth Ring Anomalies In Aleppo Pine Anomalije V Prirastnih mentioning
confidence: 99%
See 1 more Smart Citation
“…They are characterised by latewood-like cells in earlywood (E-IADF), and earlywood like cells in different portions of latewood (L-IADF) ( Figure 4). The species often have unclear growth ring bound- aries (Figure 4b) which are a consequence of uninterrupted cambial production in winter (De Luis et al, 2007De Micco et al, 2016a;Novak et al, 2016a;Balzano et al, 2018Balzano et al, , 2019a, and lack of cambial dormancy in winter (Prislan et al, 2016). The species can also contain dark rings (Figure 4b), i.e.…”
Section: Growth Ring Anomalies In Aleppo Pine Anomalije V Prirastnih mentioning
confidence: 99%
“…However, in Mediterranean and tropical environments it is often challenging to define tree rings and the boundaries between them, as their formation is not necessarily synchronised with calendar years (Cherubini et al, 2003;De Luis et al, 2011;Balzano et al, 2018Balzano et al, , 2019a. Such growth layers typically contain numerous anomalies associated with intra-annual density fluctuations (IADFs) (Campelo et al, 2007;De Micco et al, 2016a) sometimes called false rings (e.g.…”
Section: Introduction Uvodmentioning
confidence: 99%
“…V tej študiji predstavljamo možnost uporabe konfokalnega laserskega skenirnega mikroskopa Olympus LEXT OLS5000 (Olympus Corporation Tokyo 163-0914, Japonska) (Balzano et al, 2019) za identifikacijo lesa na primeru gotskega kipa svetega Jurija s Ptuja v Sloveniji (slika 1). Primerjali smo identifikacijo lesa na podlagi svetlobne mikroskopije rezin iz vzorcev, odvzetih iz kipa, nato na običajnih preparatih iz zbirke Oddelka za lesarstvo in nato še identifikacijo lesa z uporabo CLSM na vzorcih lesnih vrst, iz katerih je izdelan kip (slike 5, 8 in 10).…”
Section: Summary Povzetekunclassified
“…The tree-ring growth response of Pinus pinea during winter, previously reported for Spain and Italy (De Luis et al 2009, Natalini et al 2016, may reflect the physiological activity of this species during winter (Pardos et al 2010). Balzano et al (2019) found that in Mediterranean trees, cambium often produces several bands of alternating early-and latewood during a calendar year, resulting in the formation of IADFs. Tree-ring analysis in Pinus pinea showed a IADF region enriched in δ 13 C with an increasing trend in δ 18 O, which suggests stomatal closure, and the decrease in stomatal conductance likely contributed to the increase in δ 13 C at the IADF level (De Micco et al 2007).…”
Section: Water Use By Stone Pine Forestsmentioning
confidence: 71%
“…The high values of δ 13 C and δ 18 O, along with the larger tracheids in the IADF region of Pinus pinea, suggest an enhancement of conductive efficiency leading to strict stomatal control with the aim of avoiding dehydration (Battipaglia et al 2013). According to Balzano et al (2019), stone pine trees on the Vesuvius Mountain (near Naples, Italy) showed uninterrupted wood production from January 2015 until the end of January 2016. The authors showed differences in cambium activity in late autumn among different years; in November 2015 and 2018, the cambium was still active and no longer active, respectively.…”
Section: Water Use By Stone Pine Forestsmentioning
confidence: 99%